Calling the Police: Citizen Reporting of Serious Crime, 1979 - Spelman, William ([Verlag nicht ermittelbar], 1985)
This dataset replicates the citizen reporting component of POLICE RESPONSE TIME ANALYSIS, 1975 (ICPSR 7760). Information is included on 4,095 reported incidents of aggravated assault, auto theft, burglary, larceny/theft offenses, forcible rape, and robbery. The data cover citizen calls to police between April 21 and December 7, 1979. There are four files in this collection, one each for Jacksonville, Florida, Peoria, Illinois, Rochester, New York, and San Diego, California. The data are taken from police dispatch records and police interviews of citizens who requested police assistance. Variables taken from the dispatch records include the dispatch time, call priority, police travel time, age, sex, and race of the caller, response code, number of suspects, and area of the city in which the call originated. Variables taken from the citizen interviews include respondent's role in the incident (victim, caller, victim-caller, witness-caller), incident location, relationship of caller to victim, number of victims, identification of suspect, and interaction with police.